PENGARUH DANA INVESTASI TERHADAP PENDAPATAN KONTRIBUSI (Studi pada Perusahaan Asuransi Jiwa Syariah Yang Terdaftar di Otoritas Jasa Keuangan Periode 2016-2018) - Hanafi Hanafi; Reviyanti Reviyanti (Syar'Insurance: Jurnal Asuransi Syariah, 2020)
From the financial data contained in the tabel, visible that the investment fund to the revenue contribution on the company’s insurance sharia in Indonesia from 2016-2018 years development experience fluctuating. This study was conducted to test how much influence the investement fund to the revenue contribution of the company’s insurance sharia in Indonesia with the object of research is a life insurance company sharia which are listed on the financial services authority (OJK). Of the sampel used as many as 10 life insurance companies sharian that meet the criteria of the sample period of this research is from year 2016 to 2018 The method used in this method is a quantitative method that uses the classical aasumption test, test hypotheses, and test the coefficient of determination. the data used is secondary data obtained from official company website life insurance sharia in Indonesia. Analysis tools in this study showed a simple regression analysis involving one independent variable as a predictor of the magnitude of the predicted value of the dependen variable. The statistical analysis used was software namely SPSS Version 16.0. The results showed that the independent variables of investment funds there is a significant influence on the revenue contribution, the results of this in view of the valie of the tinag amounted to 11.513 while the value of ttable obtained from the distribution table was sought at the significance of 5% degrees of freedom (df) n-k-l or 30-1-1 = 28 then obtained a ttable of 2.04841 Therefore tinag> ttable = 11.513 > 2.04841 and significant level 0.000, because the significance value is less than 0.05, it can be concluded that H0 is rejected and Ha is accepted. The relationship between funds investment revenue contributions categorized strong and the magnitutude of the influence of investment funds on accounted for 82.6% while the remaining 17.4% is influenced by other variables not examited. The hypothesis proposed in this study is Ho is rejected and Ha accepeted. It means that investment funds are significaltly positive effect on revenue contribution.